Stability analysis for discrete-time switched systems with stable and unstable modes based on a weighted average dwell time approach. (November 2020) - Yu, Qiang; Lv, Hao
Abstract: By using a novel average dwell time approach, the stability problem for discrete-time switched systems with stable and unstable modes is investigated. First, the so-called weighted average dwell time is proposed and applied to reduce the conservativeness of stability results for the studied system whose all modes are stable. Then, combination the slow and fast weighted average dwell time, new stability criteria of discrete-time switched systems with some modes unstable are given. Third, by using linear matrix inequalities, the design of stabilizing controllers for discrete-time switched linear systems is presented. At last, two numerical examples illustrate that the new schemes have larger feasible regions for the design of switching signals than the existing results.